A study of Emirati Undergraduates Students’ Perceptions of Cooperative Learning - Al Rasbi, Sumayya Naajem (2014)
The purpose of this study is to investigate the Emirati students’ perception of using cooperative learning to progress their learning process. The study site is one of the Higher Colleges of Technology campuses in United Arab Emirates. The sample size is two hundred and twenty four participants that have been selected randomly from different programs. This study combines both the quantitative and qualitative research methods which include questionnaire and interviews to reach the final research findings and researcher recommendations. The findings of this research prove the importance of using cooperative learning to improve the students’ learning process. The final overall recommendations indicate the need to increase the usage of cooperative learning techniques to ensure a sustain improvement of students’ learning process.